MEDIA INFLUENCE ON THE IMAGE OF JOURNALISM FACULTIES IN UZBEKISTAN - Shahnoza Uzakova Beknazarovna (Journals Park Publishing, 2025)
This study investigates the role of media in shaping the public image and reputation of journalism faculties in Uzbekistan. Drawing on a multi-layered research design, the study integrates media content analysis, stakeholder interviews, and institutional document review across three major universities: O‘zJOKU, O‘zMU, and Karshi State University. Findings reveal that media coverage predominantly presents neutral narratives, with positive reporting highlighting student achievements and international collaborations, while critical content remains limited. Interviews indicate that social media platforms such as Telegram and Instagram enhance visibility and influence prospective students’ perceptions. Document analysis shows a misalignment between institutional emphasis on curriculum reforms and the focus of media coverage, which privileges easily digestible success stories. The study underscores the importance of strategic media engagement, aligning institutional narratives with public representation to enhance credibility, trust, and long-term development of journalism education in Uzbekistan.
Keywords: Journalism education, media coverage, higher education reputation, journalism in Uzbekistan, curriculum reform, social media, stakeholder perceptions, institutional communication, public image, international collaboration.